2015
DOI: 10.1111/pbr.12333
|View full text |Cite
|
Sign up to set email alerts
|

Early‐stage screening for heat tolerance in cotton

Abstract: The study aimed to identify early‐stage traits of cotton for heat tolerance using multitrait approach reflecting field yield performance. Seedling growth and physiological response of 16 cultivars to high temperature were investigated at three different developmental stages and four heat stress conditions in a climate chamber. Some traits such as hypocotyl dry weight, leaf pigment contents and cellular respiration were significantly correlated with previously known yield of ten cultivars grown in the hot field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…PCA is considered as a useful statistical tool for screening multivariate data that are highly correlated to each other (Johnson, 1998). In addition, PCA was used for classification of genotypes for heat tolerance in previous studies (Kakani et al, 2005;Liu et al, 2006;Demirel et al, 2016). The classification results of 17 genotypes for heat tolerance by using traits of cHDW, cLAI, cPn, cGs, cTr, cCT, and cSPAD exhibited a similarity to the yield performance of genotypes grown under higher temperature conditions (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…PCA is considered as a useful statistical tool for screening multivariate data that are highly correlated to each other (Johnson, 1998). In addition, PCA was used for classification of genotypes for heat tolerance in previous studies (Kakani et al, 2005;Liu et al, 2006;Demirel et al, 2016). The classification results of 17 genotypes for heat tolerance by using traits of cHDW, cLAI, cPn, cGs, cTr, cCT, and cSPAD exhibited a similarity to the yield performance of genotypes grown under higher temperature conditions (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 80%
“…PCA using SAS PROC PRINCOM (SAS Institute, 2002) was performed to classify potato genotypes for heat tolerance according to Demirel et al (2016). Values of only yield-correlated traits of 17 potato genotypes were included in the PCA.…”
Section: Methodsmentioning
confidence: 99%
“…Pettigrew [68] evaluated six cotton genotypes for their variation in photosynthetic efficiency and heat tolerance and found a very little variation among the genotypes grown in field conditions in a very natural way of inducing heat stress with mild effects, among which only a few lines were observed with reduced (15%) photosynthetic rates. In another study conducted on 16 cotton cultivars, hypocotyl dry weight, leaf pigments and cellular respiration was found affected by heat stress at different developmental stages [69]. Ahmad et al [70] observed a delay in reproductive stage initiation and accumulated higher thermal time in late maturing varieties as compared to shorter duration cultivars, by sowing at different thermal times, which also decreased the heat use efficiency of seed cotton yield.…”
Section: Physiologymentioning
confidence: 99%
“…SCY was also found to show a positive correlation with CC as reported by Demirel et al . (2016) because higher photosynthetic efficiency contributed positively towards yield. Whereas negative association was observed between CC and RCI as increasing temperature caused damage to chloroplast cells with higher RCI (Bibi et al ., 2008; Karademir et al ., 2012; Abro et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%